The Psychological and Social Experiences of Hospitalized Patients with COVID-19: A Qualitative Study - Yılmaz, Fatma Kantaş; Koca, Zeynep; Kunduracılar, Zuhal (UI Scholars Hub, 2025)
Individuals infected with coronavirus disease 2019 (COVID-19) have experienced torrents of problems associated with the pandemic, impairing their health, mental, social, and economic conditions. This study aimed to determine the psychological reactions and emotions of patients with COVID-19 infection and the social consequences during hospitalization. The current study used a qualitative and phenomenological design at a training and research hospital in Istanbul, Turkey. The study sample included 17 patients (41.6 ± 16.5 years) who had been discharged after COVID-19 treatment. The gathered information was classified into two main domains (social and psychological) and relevant themes and subthemes using a content analysis and classification method. The main factors of distress and emotions were categorized as before, during, and after hospitalization. Patients’ views of life and emotions underwent significant changes from pre-hospitalization to discharge throughout the disease course. While negative feelings such as fear, sadness, and shock/bewilderment were more prevalent before and during hospitalization, emotions concerning the value of health and life and thanksgiving dominated their psychological experiences after hospitalization. Participants experienced the social and economic impacts of COVID-19, including decreased social relationships, education, work, and income, with half experiencing stigmatization, leading to self-shyness, sadness, anger, and disappointment. The current study provided data about the psychological experiences of COVID-19 victims and their social and economic experiences, which may vary at different points throughout the disease course.